Children's Advancement Through School in Brazil: The Role of Transitory Shocks to Household Income - Suzanne Duryea (Inter-American Development Bank, Office of the Chief Economist, 1998)
This paper investigates the effects of short-run economic shocks on children`s progress through school in urban Brazil using a unique panel data set. The severe problem of grade repetition in Brazil contributes to overall low education levels. Of children ages 10-15 who are enrolled in school, only 69 percent advance on average to the next grade. This paper investigates whether children`s effort on schoolwork is diminished when parents experience a transitory shock to income.
Keywords: 330; Bildungsniveau; Schüler; Haushaltseinkommen; Schock; Brasilien